The role of iron in the pathogenesis of atherosclerosis - Kraml, P (Physiological research, 2017)
Ferritin and increased iron stores first appeared on the list of cardiovascular risk factors more than 30 years ago and their causal role in the pathogenesis of atherosclerosis has been heavily discussed since the early 1990s. It seems that besides traditional factors such as hyperlipoproteinemia, hypertension, diabetes mellitus, obesity, physical inactivity, smoking and family history, high iron stores represent an additional parameter that could modify individual cardiovascular risk. The role of iron in the pathogenesis of atherosclerosis was originally primarily associated with its ability to catalyze the formation of highly reactive free oxygen radicals and the oxidation of atherogenic lipoproteins. Later, it became clear that the mechanism is more complex. Atherosclerosis is a chronic fibroproliferative inflammatory process and iron, through increased oxidation stress as well as directly, can control both native and adaptive immune responses. Within the arterial wall, iron affects all of the cell types that participate in the atherosclerotic process (monocytes/macrophages, endothelial cells, vascular smooth muscle cells and platelets). Most intracellular iron is bound in ferritin, whereas redox-active iron forms labile iron pool. Pro-inflammatory and anti-inflammatory macrophages within arterial plaque differ with regard to the amount of intracellular iron and most probably with regard to their labile iron pool. Yet, the relation between plasma ferritin and intracellular labile iron pool has not been fully clarified. Data from population studies document that the consumption of meat and lack of physical activity contribute to increased iron stores. Patients with hereditary hemochromatosis, despite extreme iron storage, do not show increased manifestation of atherosclerosis probably due to the low expression of hepcidin in macrophages.
Keywords: makrofágy; Cardiovascular Diseases; Iron; Macrophages; hemochromatóza; ateroskleróza; zvířata; železo; oxidační stres; Humans; Oxidative Stress; Atherosclerosis; Hemochromatosis; kardiovaskulární nemoci; lidé; Animals